Bail agents and bounty hunters: Adversaries or allies of the justice system? - Johnson, Brian R. (American journal of criminal justice, 2003)
Bounty hunters are employed by the bail industry to locate and apprehend criminal defendants who “skip” bail and, subsequently, fail to appear for court appointments. While some scholars have examined bounty hunters, this work is concerned primarily with the origins, history, and legal challenges to the industry and its practices. Popular literature on this subject has created the “myth” of the bounty hunter, but it has failed to provide an accurate portrayal of the activities these individuals perform. Through the use of field research methods, this study provides a better understanding of the role that bail agents and bounty hunters play in the criminal justice system.